A synthetic, spectroscopic and computational study of copper(II) complexes supported by pyridylamide ligands. (14th December 2015) - Pauly, Magnus A.; Erwin, Ethan M.; Powell, Douglas R.; Rowe, Gerard T.; Yang, Lei
Graphical abstract: Three new copper(II) complexes supported by pyridylamide ligands were synthesized. X-ray crystal structures showed desired intra- and intermolecular interactions, which were confirmed by Hirshfeld surface analysis. The electronic structures of these complexes were illustrated by experimental evidence and computational studies. Abstract: Three Cu(II) complexes supported by pyridylamide ligands N -2-acetamidopyridine (Haap) and 2-( N -(2-pyridyl)carbamoyl)pyridine (H2pcp) have been synthesized. The structures of the three complexes have been characterized by X-ray crystallography, showing the metal sites with square pyramidal geometry in [Cu2 (Haap)2 (OAc)4 ] (1 ), trigonal bipyramidal geometry in [Cu(H2pcp)Cl2 (DMF)] (2 ) and square planar geometry in [Cu2 (2pcp)2 (OAc)2 ] (3 ). Complexes1 and2 possess the neutral form of the ligands, and exhibit interesting intra- and intermolecular interactions in the outer coordination sphere. The deprotonated form of H2pcp in complex3 displays a chelating-bridging coordination mode, giving rise to a dinuclear copper cluster. The detailed Hirshfeld surface analysis about the three complexes led to a better understanding of the weak interactions observed in X-ray crystal structures. Evidence offered by a close examination on FT-IR, UV–Vis, EPR and NMR supported the structural characterization and provided deep insights into the electronic structures of the complexes. Cyclic voltammetry studies revealed the different reduction/oxidation behavior of the metal centers in the different coordination environments. Density functional theory calculations were performed to validate the experimental evidence about the coordination structures, spectroscopic properties and electronic structures.